Removal of Pb, Cd and Cl from waelz oxide via pyrometallurgical process - (:unkn) unknown (My University, 2009)
In this study, removal of residue such as, chlorine, lead and cadmium was carried out via pyrometallurgical process by using collected condensed powder (Waelz oxide). In the previous study, Waelz oxide (containing 66.24 wt. % Zn, 0.18 wt. % Fe, 5.55 wt. % Pb, 0.0859 wt. % Cd, and 4.99 wt. % Cl) was collected through carbothermic reduction of EAF dusts at 1100 °C for 90 minutes. In the experimental series, a temperature controlled pilot scale rotary furnace was utilized. Temperature (1000, 1100, 1150, and 1200 °C) and time (0-120 minutes) were selected as reaction parameters. It was observed that the amount of lead, cadmium and chlorine in the Waelz oxide decreased with increased both time and temperature. The optimum conditions for the removal of Pb, Cd and Cl were achieved at 1200 °C for 120 minutes. As a conclusion, zinc oxide with 99.04 % purity was obtained after the refinement by volatilization process. The products obtained were characterized by X-Ray diffraction and chemical analysis techniques.
Keywords: Refining; Volatilization; Waelz oxide